Integrated Livestock-Fish Production Models for Livelihood Security in North-eastern India - Khan, M. H. (International Journal of Bio-resource and Stress Management, 2011)
Agriculture, horticulture and animal husbandry form the mianstay of food production in the hill states of India. A majority of the population lives in rural areas and depends for their livelihood on agriculture and allied enterprises. There is a tremendous pressure to step up the food production for the people of the hill states. However, the area available for cultivation is less owing to the rugged terrain and undulating topography; and there is least scope for horizontal expansion to increase the production. This calls for planned utilization of the agricultural land and water resources with an integrated approach to produce diverse food in large quantities from a unit area. Fishery can play an important role in the economic developmemt of the farming communities. The composite fish culture comprising of both Indian major carps and exotic carps would be a viable proposition and can be practiced in different elevations with suitable modifications in species combination and ratio. However, in a rural set up, fish culture becomes more economical when integrated with other agricultural and allied enterprises. In integrated livestock-fish farming, fish derives benefit from livestock dung and manure and at the same time, the livestock derives benefit from the aquaculture ponds, thus resulting in the overall development.